Make space : how to set the stage for creative collaboration - Doorley, Scott; Witthoft, Scott (John Wiley & Sons, Inc., 2012)
"If you are determined to encourage creativity and provide a collaborative environment that will bring out the best in people, you will want this book by your side at all times. You can browse it for tools to enhance teamwork, configurations to enable activities, insights about communal behaviors, design templates and first person stories. The way we design our spaces can help us or hinder us, inspire new ideas or stifle them, make it easier to work together or set us apart. Discover here how to improve team dynamics by altering your physical environment."--Bill Moggridge, Director of the Smith.